LR12 Promotes Liver Repair by Improving the Resolution of Inflammation and Liver Regeneration in Mice with Thioacetamide- (TAA-) Induced Acute Liver Failure - Yongjuan Wang; Xiaoli Xie; Hongqun Liu; Huimin Liu; Huiqing Jiang (Mediators of Inflammation)
Background. Triggering receptor expressed on myeloid cells-1 (TREM-1) controls the mobilization of inflammatory cells in response to injury and consequently enhances liver damage. LR12 is a TREM-1 inhibitory peptide. However, the role of LR12 in acute liver failure (ALF) has remained elusive. This study was aimed at indicating whether LR12 could promote liver repair in mice with thioacetamide- (TAA-) induced ALF. Methods. BALB/c mice were intraperitoneally injected with TAA, followed by intravenous injection of LR12. Damage and regeneration of the liver were assessed. LO2 cells and macrophages were used to assess the therapeutic effects of LR12. Results. Mice treated with TAA for 24 h developed ALF, while liver inflammation was alleviated after LR12 treatment. Moreover, LR12 promoted hepatocyte regeneration in mice with TAA-induced ALF. In vitro, the supernatant from TAA+LR12-treated macrophages promoted the proliferation of LO2 cells. Cytokine protein microarray analysis suggested that LR12 promoted the secretion of C-C chemokine ligand 20 (CCL20) from macrophages. Besides, neutralization of CCL20 blocked the effects of LR12, thus inhibited the proliferation of LO2 cells in vitro, aggregated the liver inflammation, and restrained hepatocyte regeneration in ALF mice in vivo. Furthermore, we also found that LR12 activated the p38 mitogen-activated protein kinase (MAPK) pathway in hepatocytes through promoting the secretion of CCL20 from macrophages. Conclusions. LR12 could improve the resolution of inflammation and liver regeneration in mice with TAA-induced ALF by promoting the secretion of CCL20 from macrophages and activating the p38 MAPK pathway. Therefore, LR12 could be an attractive therapeutic target for the treatment of ALF.